2017
DOI: 10.15282/ijame.14.2.2017.18.0347
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics investigation on total resistance coefficient of a high-speed “deep-V” catamaran in shallow water

Abstract: A reliable investigation that allows an accurate prediction of the total resistance coefficient of a high-speed" deep-V" catamaran in shallow water is obviously required. The Computational Fluid Dynamic simulation proposed approach is aimed to attain this precise outcome, while a hydrodynamic description of the rationale underlying behind the results is explained. Several effects of lateral separation ratios (S/L) and longitudinal staggered position (R/L) against a wide range of Froude numbers (Fr) from 0.5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In order to show more clearly whether the change trend of the resistance coefficient was still decreasing in a larger speed range and whether the change became more and more gentle, we visualized the data to obtain the resistance coefficient [ 33 ] with the speed (0.1 ~ 10m/s). The changes are shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to show more clearly whether the change trend of the resistance coefficient was still decreasing in a larger speed range and whether the change became more and more gentle, we visualized the data to obtain the resistance coefficient [ 33 ] with the speed (0.1 ~ 10m/s). The changes are shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Correspondingly, substantial amount of research has been carried out in late year to review the resistance characteristics of catamaran. This is necessary because resistance behavior of the catamaran is clearly different when compared to the demi hull ships [5], [6]. The effect of lateral separation ratio (S/L) between two demi hulls have revealed that the change of the lateral distance between two demi hulls on the catamaran contributed a significant effect to the resistance components [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…CFD is a reliable and practical tool to solve maritime problem such as ship towing, seakeeping and analysing the ship resistance. There are researchers such as those in [8,13,21,22], [1,3,23,24] that have been using the CFD since it can capture the hydrodynamic force and non-linear phenomenon during the simulation [1,9]. This paper proposes an analysis on heave and pitch motion of a towed ship in wave using an asymmetrical bridle towline model by using CFD.…”
Section: Introductionmentioning
confidence: 99%